Pemahaman Keluarga Muda Tentang Sakramen Perkawinan Menurut Kitab Hukum Kanonik Kanon 1055 di Paroki Santa Sesilia Keuskupan Agung Pontianak - Gunawan, Suvisius; Pongkot, Herkulanus; Dou Lodo, Mikael; Lisarani, Varetha (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2025)
The problem in this study is the low involvement of young families in church activities in the Saint Sesilia Parish, Pontianak Archdiocese. This is evident from the minimal participation of families in the celebration of Wedding Anniversary (HUP). Of the 50 family couples recorded in the Diocesan Community Data Integration Base (BIDUK) as families celebrating HUP in that month, only 6 couples participated in the HUP celebration. This research is a qualitative study with a descriptive qualitative method. The research subjects were determined by purposive sampling, consisting of six informants: four young families in the Saint Bernadinus of Siena Community, one Parish Priest of Saint Sesilia Pontianak, and one from the Family Apostolate Section coordinator. Data were collected through interviews, observation, and documentation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions using triangulation of sources and techniques to ensure data validity. Based on the research results, it was found that young families have a good understanding of the nature of Catholic marriage according to Canon 1055 §1, namely as a sacred covenant that forms a complete life partnership between husband and wife, which is eternal, open to the gift of children, and responsible for educating children in the Catholic faith. The Church through the Parish of Santa Cecilia has tried to carry out pastoral responsibilities as mandated by Canon 1063 by implementing Marriage Preparation Courses (KPP) and HUP celebrations as a form of family accompaniment. Therefore, it can be concluded that the understanding of young families in the St. Bernadinus Siena Community is good, although continuous accompaniment from the Church is still needed and implemented so that young families become more mature in faith, strong in loyalty, and able to become examples as a domestic Church in the community.